Activation of metal–organic framework materials - Mondloch, Joseph E.; Karagiaridi, Olga; Farha, Omar K.; Hupp, Joseph T. (CrystEngComm, 2013)
Crystalline metal-organic frameworks (MOFs) have emerged as a highly desirable class of solid-state materials. Some of their most attractive features include exceptionally high porosities as well as surface areas. A key aspect to the realization of high porosity is the removal of guest molecules from the framework while still maintaining its structural integrity (i.e., "activation"). This contribution highlights the strategies utilized to date for activating MOFs, including: (i) conventional heating and vacuum; (ii) solvent-exchange; (iii) supercritical CO sub(2) (scCO sub(2)) exchange; (iv) freeze-drying; and (v) chemical treatment.